Use of reabsorbing mesh in rats splenic trauma - Sánchez, Dina (2007)
Objective: To determine if use of reabsorbing mesh stops hemorrhage and avoids spleen removal in abdominal trauma. Design: Experimental study. Setting: Experimental Surgery Service, of both UNMSM and Children’s Hospital. Materials: Reabsorbing mesh (polyglycolic acid), rats, anesthesia, minor surgery equipment, materials for anatomical tissues. Interventions: Under general anesthesia rats were opened by midline incision to expose the spleen, which was injured in 1st, 2nd and 3rd degrees, then covered with reabsorbing mesh, fixing with catgut 3/0 and pressing until bleeding was restrained; then abdominal cavity was closed with vicryl 3/0. Clinical evaluation was done at 24, 48 and 72 hours post-surgery to observe survival, then re-opened randomly at 15, 30 days and 3 months to see the presence of adhesions and mesh reabsorption. Main outcome measures: Survival, adhesions, mesh reabsorption. Results: From the 60 rats with 1st, 2nd, and 3rd degree lesions 97% survived (58 rats) and 3% died (2 rats: one rat with 1º degree injury died at 24 hours because of aggression from another rat and another rat with 3º degree injury died 72 hours post op and at necropsy showed micro abscesses in mesentery and liver). At 15 and 30 days we observed intra-abdominal adhesions, and at 3 months total reabsorption of the mesh. Conclusions: Reabsorbing mesh (polyglycolic acid) is a material that restrains bleeding and avoids spleen extraction in abdominal trauma bleeding.